Libraries and the pursuit of happiness - Jefferson, Cheryl; American Library Association (Chicago : Encyclopaedia Britannica Educational Corporation, 1981)
Shows today's modern library as an active learning center and a valuable public resouce offering a variety of services, including lending books, exercise classes, special collections, and assisting the handicapped. Visits libraries throughout the United States
Keywords: Libraries; Libraries and society